Celebrating Soft Matter's 10th Anniversary: Cell division: a source of active stress in cellular monolayers. Issue 37 (7th October 2015) - Doostmohammadi, Amin; Thampi, Sumesh P.; Saw, Thuan B.; Lim, Chwee T.; Ladoux, Benoit; Yeomans, Julia M.
<x xml:space="preserve">Abstract</x> The emergence of meso-scale turbulence by division-induced active stresses in cellular monolayers.